2017
DOI: 10.1007/978-94-024-1079-2_86
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taurine and Vitamin D on Antioxidant Enzyme Activity and Lipids Profiles in Rats Fed Diet Deficient Calcium

Abstract: Calcium deficiency is a worldwide problem affecting both developed and developing countries. The deficiency in calcium leads to a marked decrease of superoxide dismutase. It is known that vitamin D protects cells against oxidative damages while taurine plays an anti-inflammatory and antioxidant role. In this study, we examined whether vitamin D and taurine supplementation had a protective effect on oxidative stress in rats fed calcium deficient diet. Female SD rats (mean weight 60 ∼ 70 g) were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…On one hand, it maintains the genomic stability of normal cells. First, it promotes the expression of DNA repair protein RAD50 and ATM, and reduces the genetic toxicity caused by chemicals ( Ting et al., 2012 ); second, 1α,25(OH) 2 D 3 promotes SOD, GSH and reduces glutathione reductase to decrease oxidant damage ( Choi and Jung, 2017 ); third, it prevents malignant transformation of prostate epithelial cells by inhibiting oxidant damage ( Bao et al., 2008 ). Most importantly, 1α,25(OH) 2 D 3 protects the lung from radiation-induced injury by inducing the proliferation of type II lung cells and the synthesis of surfactant and reducing the vascular permeability caused by radiation ( Yazici et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, it maintains the genomic stability of normal cells. First, it promotes the expression of DNA repair protein RAD50 and ATM, and reduces the genetic toxicity caused by chemicals ( Ting et al., 2012 ); second, 1α,25(OH) 2 D 3 promotes SOD, GSH and reduces glutathione reductase to decrease oxidant damage ( Choi and Jung, 2017 ); third, it prevents malignant transformation of prostate epithelial cells by inhibiting oxidant damage ( Bao et al., 2008 ). Most importantly, 1α,25(OH) 2 D 3 protects the lung from radiation-induced injury by inducing the proliferation of type II lung cells and the synthesis of surfactant and reducing the vascular permeability caused by radiation ( Yazici et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an iron-overload murine model of oxidative stress, which mimics features of chronic liver diseases (such as alcoholic liver disease and chronic viral hepatitis), taurine has been shown to reduce the accumulation of ROS, thereby exhibiting strong anti-oxidant activity ( 221 ). In another experimental setting, administration of 2% taurine (2/100 g diet) to rats fed a 50% calcium-deficient diet, has been shown to inhibit LPO in the liver, as compared to control rats ( 222 ). This makes sense if one considers that calcium is a crucial component of cholesterol and lipid metabolism and that taurine has been shown to counteract the effects of oxidative stress by regulating both calcium and lipid homeostasis ( 222 ).…”
Section: The Anti-oxidant Efficacy Of Taurine Against Hepatic- Associated Stressmentioning
confidence: 99%
“…It is confirmed that taurine restores the activities of Mn-SOD and GSH-Px in mice mitochondrion after tamoxifen infection [ 48 ]. Furthermore, Choi and Jung [ 49 ] in their studies pointed out that taurine supplementation increased hepatic SOD activity on the calcium deficiency condition, but the activities of GSH-Px and catalase (CAT) were not significantly different between normal mice and calcium deficient mice.…”
Section: Cysteinementioning
confidence: 99%